Improving milk donation behavior through an educational intervention based on the theory of planned behavior: study protocol of a cluster randomized controlled trial - Shirin Shahbazi Sighaldeh; Maryam Moridi; Vafa Ghorban Sabagh; Anoshirvan Kazemnejad; Fatemeh Shateranni (BMC, 2023)
Abstract Background Breastfeeding mothers' decisions to donate their milk is influenced by their knowledge, attitudes, and subjective norms such as their family's opinions on milk donation. In Iran, women have favorable knowledge and positive attitudes toward breastfeeding, but they lack sufficient information and education about milk banks. With respect to current childbearing policies, an increase in the number of infants who will be admitted to neonatal intensive care units is expected. Accordingly, improving milk donation behavior, which requires mothers' intention and ability to donate breast milk, is important for infants' survival and well-being. Therefore, this study aims to evaluate whether an educational program based on the theory of planned behavior affects breastfeeding mothers' decisions to donate their breast milk. Methods This cluster randomized controlled trial will be conducted in health centers affiliated to Tehran University of Medical Sciences and will enroll 66 breastfeeding mothers (intervention, n = 33; control, n = 33). After collecting baseline data, the intervention group will begin receiving a 60-minute weekly educational program based on Theory of Planned Behavior components for four weeks. The first follow-up assessment will be conducted immediately after the intervention, and the final one will be conducted 12 weeks later. The primary outcomes are the number of mothers who have donated their breast milk and changes in breastfeeding mothers' knowledge, attitude, subjective norms, and perceived behavioral control about donor human milk and intention to donate milk. Discussion This trial will evaluate if a well-designed educational program can improve breastfeeding mothers' knowledge and promote their behavioral factors regarding milk donation and lead to a significant increase in the number of potential milk donors. Trial registration irct.ir (IRCT20230124057203N1) registered February 14, 2023.